PEMBERDAYAAN MASYARAKAT PESISIR (STUDI PADA KOMUNITAS BANK SAMPAH BINTANG MANGROVE KELURAHAN GUNUNG ANYAR TAMBAK, KECAMATAN GUNUNG ANYAR, KOTA SURABAYA) - Desita Sukma Ramdhani; Tjitjik Rahaju (Publika, 2022)
Community empowerment is an effort to raise awareness and build community capacityin managing natural potential as well as being able to overcome problems in coastal areas. Garbage in the east coast of Surabaya disrupts the balance of the mangrove ecosystem which can result in environmental pollution and can endanger public health. This study aims to describe the process of empowering coastal communities through waste management carried out by the Bintang Mangrove Waste Bank community. The method used is a descriptive method with a qualitative approach. This research was analyzed using theory 3 (three) aspects of empowerment, namely enabling, empowering, and protecting.Based on the results of the research on Coastal Community Empowerment (Study on the Bintang Mangrove Garbage Bank Community, the community empowerment process was successfully carried out using waste bank media with several elements of program innovation whose benefits were intended for the community. Suggestions that could be raised were, the need to develop savings and loan programs so that they can become cooperatives and communities need to establish cooperationby expanding networks with institutions that can support waste banks. Keywords: Community Empowerment, Coast, Waste Bank, Mangrove